2014
DOI: 10.3406/bspf.2014.14362
|View full text |Cite
|
Sign up to set email alerts
|

Les pratiques ornementales à l’Aurignacien ancien dans le Centre-Ouest de la France : l’apport des fouilles récentes aux Cottés (Vienne)

Abstract: Le gisement des Cottés, situés aux marges sud-ouest du Bassin parisien, livre un abondant mobilier lithique et osseux des premières phases du Paléolithique supérieur (Châtelperronien, Protoaurignacien, Aurignacien ancien). Cette étude présente onze objets de parure découverts dans ce gisement à l'occasion des nouvelles fouilles et un artefact issu des anciennes fouilles. La série d'analyses mises en oeuvre pour ces éléments de parure met en évidence la variété des supports et des techniques utilisés pour leur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In layer 04 upper , two fox remains—a tibia distal extremity (S4-64) and a calcaneus (W8-336)—bear cut-marks that can be considered as evidence of skin recovery 38 . In addition, a recent study of the personal ornaments has identified two drilled fox canines at different stages of production confirming the in situ production of beads 36 . Associated with the cut-marked fox remains, this sustains the hypothesis of an integrate acquisition of these canines to the subsistence activities.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In layer 04 upper , two fox remains—a tibia distal extremity (S4-64) and a calcaneus (W8-336)—bear cut-marks that can be considered as evidence of skin recovery 38 . In addition, a recent study of the personal ornaments has identified two drilled fox canines at different stages of production confirming the in situ production of beads 36 . Associated with the cut-marked fox remains, this sustains the hypothesis of an integrate acquisition of these canines to the subsistence activities.…”
Section: Resultsmentioning
confidence: 67%
“…Beside reindeer resources, the Early Aurignacian deposit (US 04 upper ) shows also the exploitation of new categories of faunal raw materials for symbolic purposes. Thus the accumulation of mammoth dentine ivory remains (NISP = 4) can be put in relation with the presence in the site of personal ornament made in such material 36 . Since it is commonly accepted that such beads are made with fossil dentin 37 and since no other mammoth elements were found in the same layer, it is reasonable to assume that their accumulation did not result from hunting activities.…”
Section: Resultsmentioning
confidence: 99%
“…At Les Cottés, hyena, wolf, and fox bones with cut-marks have been found in layer 06, layer 04/upper, and layer 02. Also, mammoth ivory transformed into beads have been found into layer 04/upper ( 43 ). Carnivore and mammoth consumption are two hypotheses that have to be considered.…”
mentioning
confidence: 99%
“…Keeping in mind the small size of the object, the most salient features shared by the T21 pendant and other objects of this category are a short groove depicting the external urethral meatus and another groove for the neck (Supplementary information S8, Model3D Graphite pendant). These features-a groove at the mid-section and a short deep groove at one extremity-are observed on a limestone pebble found in the Early Aurignacian at Les Cottés (France) 62 and a long pebble with a circular groove at Hohle Fels Cave (Germany), discovered in a layer dated to 28 ka ago. Although the long pebble was used as a retoucher, it is also interpreted as a phallus representation 63 .…”
Section: Discussionmentioning
confidence: 84%